PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF LEARNING MOTIVATION OF STUDENTS (World Bulletin of Social Sciences, 2021)
The need for knowledge is one of the main human needs, on the basis of which the individual masters the centuries-old human experience. At different periods of a person's life, the objects of his interest, forms and methods of acquiring knowledge change, but the need for knowledge as an inherent property of a person, not only does not become dull over the years, but also receives its further development.
Keywords: development; become; receives; individual